2013
DOI: 10.3846/16486897.2012.721373
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of foodborne pathogens during cattle manure composting with addition of calcium cyanamide

Abstract: Inactivation of four species of foodborne pathogens (E. coli, Salmonella, E. faecalis, and S. aureus) was investigated during laboratory-scale composting of fresh cow manure with addition of calcium cyanamide (CaCN 2 ) at constant temperature conditions, and the effects of temperature and additive content of CaCN 2 on the efficacy of inactivation were evaluated. At different composting temperatures (20, 30, 37 and 50 8C), a significant inhibition or quick inactivation of pathogens were observed during 10 d com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Particularly, antibiotic-producing microorganisms in organic formulations might have played an important role in eliminating foodborne pathogens and phytopathogens (Qiu et al 2012). Similar to this, composting of cow dung was also reported to be effective in removing foodborne pathogens such as S. aureus and E. coli (Simujide et al 2013). Recently, Liu et al (2013) reported that the inoculation of antagonistic bacteria with organic formulations was found to be effective in phytopathogen control.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Particularly, antibiotic-producing microorganisms in organic formulations might have played an important role in eliminating foodborne pathogens and phytopathogens (Qiu et al 2012). Similar to this, composting of cow dung was also reported to be effective in removing foodborne pathogens such as S. aureus and E. coli (Simujide et al 2013). Recently, Liu et al (2013) reported that the inoculation of antagonistic bacteria with organic formulations was found to be effective in phytopathogen control.…”
Section: Discussionmentioning
confidence: 58%
“…and Campylobacter sp. (Simujide et al 2013). In line with this, our results also showed the presence of S. aureus and E. coli pathogens in cow dung.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous works showed that the E. coli and other pathogens could be entirely killed with the addition of CaCN 2 in the cow manure composting [10, 45]. And all of the tested E. coli strains with different types of serogroups were quickly inactivated in the compost piles added CaCN 2 [10].…”
Section: Resultsmentioning
confidence: 99%
“…A big amount of organic waste is produced because of a huge demand and relative production scale. Lifestock manure has potential negative impact on the environment and human health (Hu, Cheng, & Tao, ; Rasse et al, ; Simujide et al, ). However, these by‐products of farming can also be considered as a potential inexhaustible energy source and fertilizers (Arlauskienė, Maikštėnienė, & Šlepetienė, ; Esteves, Herrera, Esteves, & Morgado, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%